A Review of the Causes of Workplace Violence and its Preventive Measures - The Management Perspective (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
In the recent past, workplace violence has gained a lot of attention for business managers and academic researchers alike. This paper will highlight and discuss some of the causes for workplace violence along with some possible remedies based on the review of available literature and empirical analysis. The identified factors are divided into three categories i.e. Societal, economic and management related. Provide Coaching or Counseling, taking disciplinary action and to establish a violence-protection policy are among some of the possible remedies and strategies to prevent or deal with the workplace violence.